إشكالية الزمن وعوضه في عقدي السلم، والبيع الآجل: دراسة تحليلية وصفية - Saleh, M.A.A.; Ghattas, I.A.M. (Universiti Sains Islam Malaysia, 2024)
This paper purposes to discuss the basis for determining compensation in the contract of banking financing through the meanings and intentions which understood and implemented by Senior Muslim scholars in the four Sunni schools in most Muslim countries. There are several elements which must be considered in bank financing contracts, namely, goods, time, capital and time value. According to this perception is that time is the most important elements in the bank financing contracts which causes the issues of riba in the most of bank financing contract. The financing contracts are indeed considered as new kinds of contracts in the banking system. When the principle of sale contracts in Islamic jurisprudence basically represents everything in its meaning, it is inevitable that financing contracts in bank are referred to similar contracts in jurisprudence, and perhaps "salam" contract and deferred contract are the most similar contracts to the bank financing contracts. Therefore, this research is conducted on both contracts basis. In the other hand the most important reasons for divergence of views toward the issues is the elaborating the issues which began from the branch regardless determining the principles, focusing on the types. Therefore this research is attempting to discuss the basis of the rule of the value of time in the financing contracts of bank. The method of this research is to address to the views of Senior Fiqh Scholars of the four Sunni schools of analysis to reach the destinations included.